1988
DOI: 10.3109/15563658809000343
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity induced by chemicals

Abstract: Immunotoxicologic studies have demonstrated that autoimmune responses and/or autoimmune diseases are induced in humans and experimental animals by chronic exposure to various chemicals. The present review is focused on seven groups of chemically induced human disorders, i.e. systemic lupus erythematosus, autoimmune hemolytic anemia, myasthenia gravis, pemphigus, glomerulonephritis, thyroiditis and hepatitis. Results obtained from studies of the available experimental counterparts of these diseases, i.e. those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 66 publications
2
33
0
1
Order By: Relevance
“…The study of murine Hg-induced autoimmunity is important because of the many reported associations between various drugs, chemicals, or pollutants and human autoimmune diseases [18,19]. Heavy metals are frequent environmental pollutants and ANoA were detected by immunofluorescence on HEp-2 cells using isotype-specific FITC conjugates [14].…”
Section: Discussionmentioning
confidence: 99%
“…The study of murine Hg-induced autoimmunity is important because of the many reported associations between various drugs, chemicals, or pollutants and human autoimmune diseases [18,19]. Heavy metals are frequent environmental pollutants and ANoA were detected by immunofluorescence on HEp-2 cells using isotype-specific FITC conjugates [14].…”
Section: Discussionmentioning
confidence: 99%
“…A number of chemical and environmental agents as well as pharmaceuticals may lead to autoimmune diseases in experimental animals or humans [Bigazzi, 1988;Kammuller et al, 1989]. The consequences regarding the effects of immunosuppression/depression in humans have been extensively studied.…”
Section: Consequences Of Immunotoxicitymentioning
confidence: 99%
“…10 Os sais de mercúrio e vapores de Hg têm sido usados como modelo de indução de glomerulonefrite em determinadas cepas de ratos, Brown Norway e Wistar rats. 68 Estudos sobre imunoglobulinas e outros parâme-tros imunológicos têm sido realizados em trabalhadores expostos a altas e a baixas concentrações de mercúrio, comparando-os a um grupo-controle.…”
Section: Manifestações Renais E Alterações Imunológicasunclassified